2022
DOI: 10.3389/fpsyg.2022.833279
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation of Learning and EFL Learners’ Hope and Joy: A Review of Literature

Abstract: One of the new structures of positive psychology that has received special attention is academic self-regulation. It involves controlling one’s behavior, emotions, and thoughts to reach a long-term purpose. Learning how to self-regulate is an important skill that language learners learn both for emotional maturity and later social connections. There are various emotional factors that might be associated with the notion of self-regulation. Hope and joy are among the emotional factors that might influence langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Other systematic reviews go along the same lines, and in the same journal and section Frontiers in Psychology . For example, Dickson and Schubert ( 2020 ) and Liu et al ( 2022 ) found only six studies in a review of great interest; the study by Nguyen et al ( 2021 ) identified 18 eligible articles; Shou et al ( 2022 ) with 12 studies included; or Tarchi et al ( 2021 ); Huang ( 2022 ) found seven studies for quantitative analysis and eight for indirect evidence; Coxen et al ( 2021 ) with 21 articles included in the focal analyzes of the systematic review. The number of studies to be representative is not defined by the number but by the existence of such studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other systematic reviews go along the same lines, and in the same journal and section Frontiers in Psychology . For example, Dickson and Schubert ( 2020 ) and Liu et al ( 2022 ) found only six studies in a review of great interest; the study by Nguyen et al ( 2021 ) identified 18 eligible articles; Shou et al ( 2022 ) with 12 studies included; or Tarchi et al ( 2021 ); Huang ( 2022 ) found seven studies for quantitative analysis and eight for indirect evidence; Coxen et al ( 2021 ) with 21 articles included in the focal analyzes of the systematic review. The number of studies to be representative is not defined by the number but by the existence of such studies.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the seminal research conducted by Dewaele and MacIntyre (2014), which pioneered the examination of both positive and negative emotions, a subsequent proliferation of empirical studies on emotions in the field of second language acquisition (SLA) has occurred. This body of research includes positive emotions, particularly enjoyment, joy, and hope (Dewaele, Botes, & Greiff, 2023;Huang, 2022;Johnson, 2019;MacIntyre, Mercer, Gregersen, & Hay, 2022;Zhao, 2023), along with negative emotions such as anxiety, anger, distress, sadness, and shame (Teimouri, Goetze, & Plonsky, 2019). However, other emotions commonly experienced by learners, such as foreign language learning boredom (FLLB), have received less attention in the literature and remain underexplored (Li, 2022;Li & Dewaele, 2020;Li & Wei, 2022;Zhao & Wang, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported that self-regulation plays important role in learning, for example learning the second language (Khodarahmi & Zarrinabadi, 2016;Alzubaidi, Aldridge & Khine, 2016;Huang, 2022;Wijaya & Setiawan, 2021), mathematical problems (Perels, Dignath & Schmitz, 2009;Labuhn, Zimmerman & Hasselhorn, 2010), science (Li, Zheng, Liang, Zhang & Tsai, 2016), and medical education (Siddaiah-Subramanya, Nyandowe & Zubair, 2017). Thus, self-regulation in learning will influence academic achievement (Schapiro & Livingston, 2000;de Acedo Lizarraga, Ugarte, et al, 2003;Vermunt, 2005;Labuhn, Zimmerman & Hasselhorn, 2010), and professional career (Endedijk, Referring to the previous explanations, then the issue to be raised in this study was what variables of self-regulated learning that support students' academic achievement.…”
Section: Introductionmentioning
confidence: 99%